2016 18th Mediterranean Electrotechnical Conference (MELECON) 2016
DOI: 10.1109/melcon.2016.7495414
|View full text |Cite
|
Sign up to set email alerts
|

SoundPacman: Audio augmented reality in location-based games

Abstract: Sound design has received little attention in location-based games research. Typically, existing prototypes heavily rely on visual information with sound only having a marginal role in the game design and development process. This paper investigates the role of sound as primary interface for conveying game information and creating engaging gaming experiences. As a case study, we present SoundPacman, a prototype location-based game, wherein players experience the game space with the use of 3D sounds, which augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 9 publications
0
26
0
4
Order By: Relevance
“…Observação de uso foi o segundo mais aplicado (14 estudos, 60,87%), seguindo uma tendência comum de vincular entrevistas a algum tipo de observação [30]. Vale destacar que apenas dois (8,70%) estudos [10,56] utilizaram monitoramento de dados fisiológicos -ambos aplicaram também entrevista, observação e registro de logs de interação. Uma possível explicação para a baixa utilização desses métodos é que a avaliação de JBL, idealmente, é feita em ambientes externos ou que simulem contextos de mobilidade, o que pode dificultar o uso de alguns dos equipamentos que capturam essas medidas.…”
Section: Uso De Entrevistas No Mapeamento Sistemáticounclassified
“…Observação de uso foi o segundo mais aplicado (14 estudos, 60,87%), seguindo uma tendência comum de vincular entrevistas a algum tipo de observação [30]. Vale destacar que apenas dois (8,70%) estudos [10,56] utilizaram monitoramento de dados fisiológicos -ambos aplicaram também entrevista, observação e registro de logs de interação. Uma possível explicação para a baixa utilização desses métodos é que a avaliação de JBL, idealmente, é feita em ambientes externos ou que simulem contextos de mobilidade, o que pode dificultar o uso de alguns dos equipamentos que capturam essas medidas.…”
Section: Uso De Entrevistas No Mapeamento Sistemáticounclassified
“…AR menjadi cara komunikasi konten yang baru, sebagai kombinasi teks, 3D model, video, yang memberikan perspektif baru [5] [6]. Penelitian terbaru menemukan bahwa penggunaan 3D digital objek yang di aplikasikan ke lingkungan fisik dapat menghasilkan pengalaman yang signifikan [7] [8]. Dalam survey yang di lakukan saat ini teknologi Augmented Reality sangat sesuai untuk di implementasi dalam pembelajaran [9].…”
Section: Pendahuluanunclassified
“…Audio feedback can also affect the user's understanding of visual space, and deliberately misaligned audio and visual information may lead to better perception of space in virtual scenes [17]. In addition, audio design can also serve as the primary interface for the transmission of game information and create engaging gaming experiences in location-based AR games [18]. Auditory interfaces for aviation applications have also been studied by NASA; for example, studies found that using spatialized sound to guide head direction could make a great reduction in visual acquisition time [19].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Therefore, we are not using specially developed devices but deliberately use a standard consumer smartphone and its standard features. Rhythm can be a very effective aid in nonvisual displays [18], and amplitude has also been used to present haptic and audio display information [19]. Smartphones can well support variation in the rhythm and amplitude of haptic and audio feedback; thus, we used rhythm and amplitude in nonvisual feedback designs to present information and investigated the effects of different interaction designs.…”
Section: Study 1: Nonvisual Display Design For Information Representamentioning
confidence: 99%